Critical Analysis of Rational Emotive Behavior Therapy Approaches: Ethics and Values in Counseling - Prasetia, Agung Tri; Firman, Firman; Ahmad, Riska; Harmalis, Harmalis (Universitas Negeri Padang, 2022)
This article will begin with an overview of REBT theory before moving on to a discussion of the ethics governing the field of psychology. This paper will try to answer the question whether Ellis's (1955) REBT theory can be used independently during therapy sessions, or whether it requires a combination of ethics and values to provide the best service to clients or not. Ethical considerations must be applied to the application of theory to improve it and make it more useful in therapy sessions, therefore it is important to determine how well theory can function on its own while still meeting the needs of its clients.